2022
DOI: 10.1097/01.nep.0000000000001062
|View full text |Cite
|
Sign up to set email alerts
|

A National Report on Clinical Judgment Model Use in Prelicensure Nursing Curricula

Abstract: AIM This study examined US prelicensure nursing program use of clinical judgment models and teaching strategies to promote students' clinical judgment. BACKGROUND Growing interest in teaching clinical judgment associated with upcoming changes in NCLEX-RN testing warrants exploration of how models and teaching strategies are currently used. METHOD A cross-sectional survey with multiple-choice and open-ended response items was used to examine programs' use of clinical judgment educational models. RESULTS Of 234 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The survey was developed by a group of researchers with significant experience related to clinical reasoning and judgment. Survey items were designed to elicit practices in model use (described elsewhere 20 ), teaching strategy use for the specific purpose of developing clinical reasoning and judgment (response options listed in the Table ), and beliefs about how the choice to use or not use teaching strategies to promote clinical reasoning and judgment is influencing student outcomes.…”
Section: Survey Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The survey was developed by a group of researchers with significant experience related to clinical reasoning and judgment. Survey items were designed to elicit practices in model use (described elsewhere 20 ), teaching strategy use for the specific purpose of developing clinical reasoning and judgment (response options listed in the Table ), and beliefs about how the choice to use or not use teaching strategies to promote clinical reasoning and judgment is influencing student outcomes.…”
Section: Survey Developmentmentioning
confidence: 99%
“…For reporting purposes, the number and types of teaching activities used were analyzed by model use status, as described in the article reporting first results of the larger study. 20 Qualitative A qualitative research expert who was not part of the research team conducted a preliminary analysis of the data for differences among program types and use or nonuse of a clinical judgment model, identified codes, and proposed themes. Members of the research team separately coded and categorized the data.…”
Section: Data Analysis Quantitativementioning
confidence: 99%
See 1 more Smart Citation
“…A recent national survey showed that some nursing programs use clinical judgment models (CJMs) to promote the development of students' clinical judgment and prepare students for the Next Generation NCLEX®. CJMs are used to guide curriculum design and provide a framework for implementing effective teaching strategies for clinical judgment development (Jessee et al, 2023).…”
mentioning
confidence: 99%
“…Several models illustrate clinical judgment in nursing. Tanner’s model of clinical judgment, the most widely used in US nursing education programs that use a model (Jessee et al, 2023), describes the influence of contextual factors and the nurse’s background and relationship with the client (Tanner, 2006). Tanner’s model provides an iterative process that incorporates key elements of background information and provides steps for making clinical decisions: noticing, interpreting, responding, and reflecting.…”
mentioning
confidence: 99%